2013
DOI: 10.1080/09297049.2013.792332
|View full text |Cite
|
Sign up to set email alerts
|

AULA virtual reality test as an attention measure: Convergent validity with Conners’ Continuous Performance Test

Abstract: The majority of neuropsychological tests used to evaluate attention processes in children lack ecological validity. The AULA Nesplora (AULA) is a continuous performance test, developed in a virtual setting, very similar to a school classroom. The aim of the present study is to analyze the convergent validity between the AULA and the Continuous Performance Test (CPT) of Conners. The AULA and CPT were administered correlatively to 57 children, aged 6-16 years (26.3% female) with average cognitive ability (IQ mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 19 publications
7
90
2
3
Order By: Relevance
“…We further propose that the consistent inconsistency also appeared on tasks measuring reaction time of auditory attention. This result support the finding of a recent study (Díaz-Orueta et al, 2014), which adopt the CPT developing in a virtual setting to explore similar topic, stated the importance of reaction time variability, a measure of consistency of attention, in both auditory and visual attention of children with ADHD.…”
Section: Reaction Time Variabilitysupporting
confidence: 93%
“…We further propose that the consistent inconsistency also appeared on tasks measuring reaction time of auditory attention. This result support the finding of a recent study (Díaz-Orueta et al, 2014), which adopt the CPT developing in a virtual setting to explore similar topic, stated the importance of reaction time variability, a measure of consistency of attention, in both auditory and visual attention of children with ADHD.…”
Section: Reaction Time Variabilitysupporting
confidence: 93%
“…Another virtual classroom test is the AULA (Spanish for "Classroom") test (Iriarte et al, 2016) that comprises visual and auditory No-X and X tasks (with and without distracters) and two measures of motor activity. Díaz-Orueta et al (2014) could show that the AULA test is suited to differentiate between medicated and unmedicated children in various measures related to the ADHD symptom clusters. Accordingly, these studies suggest that the VRC-CPT and the AULA test are apt tools to assess all symptom clusters in ADHD children.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that virtual classrooms could bring higher ecological validity of the results than other assessment instruments (Díaz-Orueta et al, 2014). Based on the empirical studies with virtual classrooms, it is believed that examining the redundancy effect in electronic slideshow assisted lecturing with the use of the virtual classroom as an empirical study platform could bring the results that are similar to those found in the normal classrooms.…”
Section: Introductionmentioning
confidence: 88%
“…Virtual classrooms have already been used in many studies, for example, in the studies assessing children with attention deficit/hyperactivity disorder (ADHD) (e.g., Díaz-Orueta et al, 2014;Rizzo et al, 2006Rizzo et al, , 2012. These studies indicated that virtual classrooms could bring higher ecological validity of the results than other assessment instruments (Díaz-Orueta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%